Quality of life experienced by South Sudanese lower limb prosthetic users after rehabilitation - Lotto Charles Paul Dominsiano; Surona Visagie (African Journal of Disability)
Background: Prosthetic rehabilitation modifies functional limitations and psychological challenges caused by amputations, as it helps to restore mobility and body image. A physical rehabilitation centre in Juba, South Sudan, has been providing prosthetic rehabilitation since 2009 in this conflict torn part of the world.